A STUDY ON PASSENGERS' FLIGHT TIME PREFERENCE - Degirmenci, Elif; Akca, Zeliha; Basligil, Huseyin (YILDIZ TECHNICAL UNIV, 2016)
First of the major problems of an airline to be solved is creation of optimum wave tariff structure based on the development and frequency of the routes. Airlines are making great efforts to build this structure. In doing so, it is important to keep in mind the preference and satisfaction of passengers. Because, placement of the flights in the hours which are not preferred will bring the missing passengers. This study has tried to put forward the passenger preferences according to passenger departures and arrivals from all over the world. Routes in the study were grouped according to similar passenger preferences. O & D-based ticket data was used (MIDT was used as data source) and for more than 100,000 O&D, time-based distribution of the passengers from relevant origin to all destinations and passengers from all origins to the relevant destination were shown. Thus, the study aims to provide decision support to airlines in tariff planning process.
Keywords: Schedule; flight schedule; passenger preference; flight time; time preference; Engineering